Comparison in Mean Amniotic Fluid Index with Omega-3 Fatty Acids vs Placebo in Cases of Unexplained Oligohydramnios - Rabia Wajid, Zainab Zubair, Asia Parveen, Nida Gulzar, Somer Masood (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Oligohydramnios is hazardous for fetal health for which new treatment modalities are being sought out. The fetus floats in amniotic fluid which takes care of its proper development. Omega-3 Fatty acids protect against inflammation and raised blood pressure. With omega-3, AFI can be improved and the complication scan be reduced leading to an overall better fetal outcome. Aim: To compare the mean amniotic fluid index with omega-3 polyunsaturated fatty acids supplementation versus placebo for management of cases of unexplained oligohydramnios Methods: A randomized control trial was held at Gynecology Unit 2, Lady Willingdon Hospital, Lahore from 21-12-2020 to 21-06-2022. 60 females were recruited to the study and randomly divided into two groups. Group 1 treated with omega-3 once capsule daily contained 1000 mg. of fish oil and group 2 treated with placebo. After 4 weeks, females were subjected to ultrasonography by a single senior sonologist with assistance of researcher. All the collected data was analyzed on SPSS version 21. Mean AFI was compared in both groups by use of independent sample t-test taking p-value<0.05 as significant. Results: Mean age in omega-3 group was 25.63±3.57 years, and in placebo group was 25±2.704 years. 22(36.67%) females were nulliparous. The mean change of AFI with omega-3 was 4.90±1.185 and with placebo group was 2.93±0.944 (p-value=<0.001). Conclusion: it was inferred that by supplementingomega-3 polyunsaturated fatty acids showed better results in terms of mean AFI than placebo for management of cases of unexplained Oligohydramnios. Keywords: Omega-3 Polyunsaturated, Amniotic Fluid Index, Unexplained Oligohydramnios